2017
DOI: 10.1016/j.jep.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of “Yahom” as a traditional Thai herbal therapy: A systematic review

Abstract: Most studies supported declared objectives relating to perceived Yahom actions, but lacked background demonstrating clinical efficacy, and mechanistic data that would validate conclusions. Our study suggests that research into traditional medicinal herbs needs underpinning by appropriate clinical interventions and pharmacovigilance, thereby optimising efficacy and minimizing toxicity by combining traditional wisdom and modern testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Recent studies have focused intensively on the discovery of new antimicrobial compounds from a wide variety of plants ( Chootip et al., 2017 ) in relation to human disease-causing microbes. It has also been observed that there is an increased interest in the development of sustainable antifungal agents, such as plant-based essential oils and extracts, to combat plant diseases ( Costa et al., 2000 ; Rahman et al., 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have focused intensively on the discovery of new antimicrobial compounds from a wide variety of plants ( Chootip et al., 2017 ) in relation to human disease-causing microbes. It has also been observed that there is an increased interest in the development of sustainable antifungal agents, such as plant-based essential oils and extracts, to combat plant diseases ( Costa et al., 2000 ; Rahman et al., 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several polyherbal preparations have been prescribed in Thai traditional medicine. A few formulas, such as Benja Amarit [ 26 ], Ya-hom [ 27 ], Jatu-Phala-Tiga [ 28 ], have been scientifically proven to exhibit biological activities related to their traditional use. In the present study, the traditional herbal medicine described in the Worayokasan scripture named Nawametho decoction was chosen because it has been used as an alternative treatment for borderline hyperlipidemic patients at Ban Ta Khun Hospital (Surat Thani, Thailand).…”
Section: Introductionmentioning
confidence: 99%
“…Their fragrant resinous wood has long been used in Ayurvedic and traditional medicine for treatment of various illness such as joint pain, inflammatory-related disorder, diarrhea, and also used as a sedative, stimulant and cardio-protectant 1 . In Thailand, agarwood is the main ingredient in the herbal remedy called “Yahom” used for treatment of fainting and abdominal discomfort 2 . Several reports describe biological activities in the resin derived from heartwood and in the leaves of Aquilaria spp 1 .…”
Section: Introductionmentioning
confidence: 99%